High yield and quality charcoal from oil palm kernel shell with an improved pilot-scale continuous carbonisation system - Nahrul Hayawin, Z; Astimar, A A; Ibrahim, M F; Noorshamsiana, A W; Ropandi, M (Malaysian Palm Oil Board, 2022)
The present study compared the production, quality, and yield of charcoal manufactured from oil palm kernel shell (OPKS) via an improved pilot-scale continuous carbonisation system, the pilot rotary kiln (PRK), with a batch conventional carbonisation approach, the Taki carbonisation system (TCS). Previous investigations demonstrated that the PRK was highly energy-efficient at 55% compared to 38% in TCS. Furthermore, the PRK attained a higher OPKS-charcoal yield at 30 ± 2.4% than TCS, which produced 22 ± 1.7%. The improved system was a self-sustaining carbonisation process that could continuously run for 8 hr, whereas the TCS required 72 hr to convert the same amount of OPKS into charcoal. A good quality charcoal (83.7 ± 2.0% fixed carbon, 10.2 ± 1.4% volatile matter, 6.1 ± 1.2% ash, and 33.1 ± 1.8 MJ kg−1 higher heating value) was also acquired via the PRK. The present study also demonstrated that the PRK approach was more financially feasible than TCS as it was projected to require lower capital cost and a higher benefit-to-cost ratio (B:C), which palm oil mill operators could achieve.